Inside pass predicts ball possession effectiveness in NBA basketball - Courel-Ibanez, J.; McRobert, A. P.; Toro, E. O.; Velez, D. C. (International Journal of Performance Analysis in Sport, 2016)
The aims of this study were to analyse the effects of using inside pass on ball possession effectiveness and to identify game performance indicators to predict inside pass success in the National Basketball Association (NBA), considering situational variables. A total of 4207 closed ball possessions (± 10 points difference) where recorded from 25 matches of the 2010 NBA Playoffs series. Ball possessions were classified whether including inside pass (n=808) or not (n=3399). Predictive analysis of use and effectiveness was made through a series of binomial logistic regressions and Classification tree analysis (CHAID). Results indicate that ball possessions including inside pass were more effective and longer in duration, finding a greater use in top-4 NBA teams regardless the game period. Additionally, inside pass effectiveness was influenced by: the receiver attitude, reception distance, and defensive help. Particularly, the analysis of combined performance indicators disclosed relevant information on attack effectiveness, suggesting players to adopt a dynamic attitude in the weak side before getting the ball, while their teammates are developing individual and collective actions to create free space and enhance inside game options and effectiveness. Current findings shed some light on specific knowledge concerning tactical behaviours in NBA basketball, contributing in the design of specific programmes to increase inside game options and players' decisionmaking according to specific game constraints.